ANALISIS HASIL PERCOBAAN ALAT PRAKTIKUM RUGI-RUGI ALIRAN DALAM PIPA - Yusuf, Nefli; Hariadi, Hariadi (Rang Teknik Journal, 2021)
The phenomenon of flow in a pipe is one of the experiments carried out in the Mechanical Phenomenon Practicum in bachellor of Mechanical Engineering. In this paper, we will describe the experimental results of the tool that was made in mechanical engineering prgram, west sumatera muhammadiyah university for the first time. The pump used is large enough to 1.0 HP, it is expected that the pressure will be high enough and cause turbulent flow. Measuring instruments installed are Pressure Gauge, Stopwatch, and Water Meter. Water is pumped from the source (reservoir) in the form of a tub to a network of pipes with diameters of ¾ ", ½" and 5/8 "by installing pressure sensors at the pump output and each of pipe. The water meter is useful for measuring the rate of water, resulting in greater flow losses. At the greater the flow velocity, resulting in a large Reynolds Number, while the velocity, at this time, namely by measuring the output capacity of 5 ml which is then measured the time needed using a stopwatch. The variation of the water flow rate is made by distinguishing the valve openings, namely 4/4 total openings then ¾, ½ and ¼. The experimental results show that the smaller the valve opening than the smaller the flow rateflow friction loss has not so effect because of the flow is in turbulent conditions. The design of this experimental tool is in compliance with the friction theory of fluid flow in pipes, closed flow, for the next stage it is necessary to develop a tool by entering the length per diameter factor (parameter)of the circulation pipe, further for laminar flow where the sensitivity of the Reynolds number has more effect on friction losses so need the precision measurement tools.